Front Cover: Microfluidic Visible‐Light Paternò–Büchi Reaction of Oxindole Enol Ethers (Eur. J. Org. Chem. 43/2020). Issue 43 (4th November 2020) - Franceschi, Pietro; Mateos, Javier; Vega‐Peñaloza, Alberto; Dell'Amico, Luca
Abstract : The Front Cover shows the Paternò–Büchi transformative process of oxindoles and ketones into oxetanes. The realisation of the process make use of light and a microfluidic apparatus. At the center of the scene the alchemist is personified as a birdman and represents both a scientist and an artist, a symbol of wisdom. This figure is sitting at a table drawing the desired molecule which become real by using the pigments that emerge from a series of microfluidic conduits. From the back wall Emanuele Paternò is observing the scene. The cover picture has been inspired by the painting "Creation of the Birds" by the Mexican‐Spanish painter Remedios Varo. More information can be found in the Communication by A. Vega‐Peñaloza, L. Dell'Amico et al.